Identifying Root Causes of Low Performance Ratings Among Mathematics Faculty: A Case Study - Manalaysay, Ellenita; Balilla, Jeffhraim; Arellano, Ma. Concepcion (Journal of Interdisciplinary Perspectives, 2025)
This study examines the root causes of consistently low Individual Performance Commitment and Review (IPCR) ratings among the mathematics faculty of a Philippine state university. Grounded in the Strategic Human Resource Management (SHRM) framework and Goal-Setting Theory, the research employed an explanatory case study design to explore faculty perceptions through three focus group discussions (FGDs) involving 22 instructors and professors. Data were analyzed using the 5 Whys technique and causal factor charting, identifying five primary issues: unattainable performance standards, inadequate understanding of the IPCR system, excessive workload, low research self-efficacy, and limited access to training and extension opportunities. These findings reveal structural and perceptual barriers to faculty performance, with implications for institutional policy, faculty development, and the refinement of performance appraisal systems. Institutions can foster a more effective and motivated academic workforce by aligning performance expectations with realistic goals and enhancing capacity-building initiatives.